Characterizing the Spatial Pattern Changes of Urban Heat Islands in Metro Manila Using Remote Sensing Techniques - Pereira, Rosalyn A.; Lopez, Epifanio D. (Philippine Engineering Journal; Vol 25 No 1 (2004))
This study characterizes the spatial pattern of urban heat island (UHI) phenomenon when in situ measurements are not available. Images obtained from remote sensors operating in the thermal infrared wavelength of Landsat Thematic Mapper (TM) and Enhanced Thematic Mapper (ETM+) were used to derive the surface temperature of Metro Manila from 1989 to 2002; thereon, the formation of urban surface heat islands became apparent. The impact of urbanization to surface urban temperature is noticeable– the average annual rate of urban growth is found to be 1.33 percent while the rise of UHI has an annual growth rate of 0.8 degrees Celsius. Likewise, increase in land surface temperature is related to the decrease in leaf biomass. These were evident from changes in land cover parameters such as fractional vegetation cover and surface moisture availability. These parameters were derived by computing the normalized difference vegetation index (NDVI) from the images.